The Multifaceted Role of VIRMA, a Core Component of the Methyltransferase Complex, in Cancer and Cancer Therapy - Jinmeng Lu; Chengyu Zhang; Mengshuang Yin; Huili You; Chao Xiong; Jing Wu; Ying Gong; Zhangang Xiao; Jing Shen (Biomolecules)
VIRMA (also known as KIAA1429), as a core regulatory subunit of the m6A methyltransferase complex, plays a key role in tumorigenesis and progression by dynamically regulating RNA methylation modifications. Studies have shown that VIRMA is aberrantly overexpressed in more than 20 types of malignant tumors, including liver cancer, breast cancer, and lung cancer, and is significantly associated with chromosome 8q amplification and poor prognosis. Its mechanism of action involves regulating the expression of tumor-associated genes through both m6A-dependent and m6A-independent pathways, thereby promoting tumor proliferation, metastasis, and drug resistance. These findings suggest that VIRMA has the potential to serve as a pan-cancer diagnostic and prognostic biomarker. This review summarizes the role of VIRMA in malignant tumors from multiple perspectives and explores its potential applications in clinical diagnosis and treatment.